ISOLASI SENYAWA 2-GERANIL-2’,3,4,4’-TETRAHIDROKSI DIHIDROKALKON DARI DAUN SUKUN (Artocarpus altilis (Park.) Fosberg) DENGAN FLASH COLUMN CHROMATOGRAPHY: Isolation of 2-Geranyl-2',3,4,4'-Tetrahydroxy Dihydrochalcone from Breadfruit Leaf (Artocarpus altilis (Park.) Fosberg) Using Flash Column Chromatography - Yumni, Gharsina Ghaisani; Pertiwi, Krisna Kharisma; Widiyastuti, Yuli; Fakhrudin, Nanang (Universitas Tidar, 2023)
Breadfruit is one of the Indonesian plants traditionally used in medication. The main active compound in breadfruit leaves is a geranylated flavonoid namely 2-geranyl-2',3,4,4'-tetrahydroxy dihydrochalcone (GTD). Previous study showed that the separation and isolation of GTD from sukun leaves is time consuming and laborious as it requires a long procedure (extraction, liquid-liquid partition, Vacuum Liquid Chromatography (VCC), Sephadex Column Chromatography (SCC), and preparative Thin Layer Chromatography (TLC). This process is ineffective and inefficient. Thus, the more effective and shorter method of isolation is needed. This study aimed to isolate GTD from breadfruit leaves utilizing flash column chromatography (FCC). The breadfruit leaves were extracted using ethanol and the extract was partitioned with the solvent n-hexane: ethyl acetate: methanol: water (3:1:3:1). The lower phase containing GTD was subjected to VCC and the fraction containing GTD was purified with FCC (using n-hexane, ethyl acetate, and methanol in a gradient polarity as mobile phases; and silica gel as a solid phase) to isolate GTD. The isolated GTD was analyzed by thin-layer chromatography (TLC) and purity was determined using high-performance liquid chromatography. This method was able to produce 138 mg of GTD (purity of 88.49 %) from 15 g of breadfruit leaf extract (0.92% yield). This study demonstrated that GTD, a main bioactive compound of breadfruit leaves, could be effectively isolated by using FCC instead of SCC and preparative TLC.